The Effect of Guided Inquiry Learning Model Assisted by Mind Map Toward Students’ Science Cognitive Competency at the VIII Grade of SMP Negeri 27 Padang - Idia Ofela Nova; Fitri Arsih; Relsas Yogica; Lufri Lufri (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The low science cognitif competency of students is caused by several problem encountered during the learning process, between the learning model that is applied has not involved students actively in the learning process. One of the efforts that is done to increase students' learning competencies in science is to apply the Guided Inquiry learning model assisted by Mind Map. This learning assisted by the Mind Map guides students to be active. This study aims to reveal the influence of the use of the Guided Inquiry learning model assisted by Mind Map to the learning competencies of science students. This research was conducted at SMP Negeri 27 Padang. in material of KD 3.7 about Circulatory System. This research is an experimental research using the Randomized Control Group Posttest Only Design. The study population was all grade VIII students of SMP Negeri 27 Padang. Sampling was taken by using purposive sampling technique. The control class used a conventional learning model which is commonly used in the class and experimental class using the Guided Inquiry learning model assisted by Mind Map. The research instrument used was a test of learning outcomes. The results of the t test were known that in the knowledge competency tcount> t table (2.76> 1.67). This showed that the hypothesis was accepted. So, it can be concluded that the Guided Inquiry learning model assisted by Mind Map has a positive effect on students' learning cognitive competencies in science.